Nominal wage rigidities in a new Keynesian model with frictional unemployment - Vincent Bodart; Gregory De Walque; Olivier Pierrard; Henri R. Sneessens; Raf Wouters (National Bank of Belgium, 2006)
In this paper, we propose a search and matching model with nominal stickiness à la Calvo in the wage bargaining. We analyze the properties of the model, first, in the context of a typical real business cycle model driven by stochastic productivity shocks and second, in a fully specified monetary DSGE model with various real and nominal rigidities and multiple shocks. The model generates realistic statistics for the important labor market variables
Keywords: E31; E32; E52; J64; 330; DSGE; Search and Matching; Nominal Wage Rigidity; Monetary Policy; Lohnrigidität; Verhandlungstheorie des Lohnes; Dynamisches Gleichgewicht; Theorie; USA